Machine learning models to prognose 30-Day Mortality in Postoperative Disseminated Cancer Patients. (September 2022) - Ganguli, Reetam; Franklin, Jordan; Yu, Xiaotian; Lin, Alice; Lad, Rishik; Heffernan, Daithi S.
Abstract: Patients with disseminated cancer at higher risk for postoperative mortality see improved outcomes with altered clinical management. Being able to risk stratify patients immediately after their index surgery to flag high risk patients for healthcare providers is vital. The combination of physician uncertainty and a demonstrated optimism bias often lead to an overestimation of patient life expectancy which can precent proper end of life counseling and lead to inadequate postoperative follow up. In this cohort study of 167, 474 postoperative patients with multiple types of disseminated cancer, patients at high risk of 30-day postoperative mortality were accurately identified using our machine learning models based solely on clinical features and preoperative lab values. Extreme Gradient Boosting, Random Forest, and Logistic Regression machine learning models were developed on the cohort. Among 167, 474 disseminated cancer patients, 50, 669 (30.3%) died within 30 days of their index surgery; After preprocessing, 28 features were included in the model development. The cohort was randomly divided into 133, 979 patients (80%) for training the models and 33, 495 patients (20%) for testing. The extreme gradient boosting model had an AUC of 0.93 (95% CI: 0.926–0.931), the random forest model had an AUC of 0.93 (95% CI: 0.930–0.934), and the logistic regression model had an AUC of 0.90 (95% CI: 0.900–0.906 the index operation. Ultimately, Machine learning models were able to accurately predict short-term postoperative mortality among a heterogenous population of disseminated cancer patients using commonly accessible medical features. These models can be included in electronic health systems to guide clinical judgements that affect direct patient care, particularly in low-resource settings. Highlights: Machine Learning in risk modeling for disseminated cancer. Applicable in low resource settings across many cancer types.